VOLODYMYR ANTONOVYCH: THE PATH TO THE BOSOM OF THE FOUNDERS OF THE UKRAINIAN HISTORICAL SCHOOL - Ткаченко, Вадим (SWorldJournal, 2024)
The article examines the life and work of Volodymyr Bonifatiyovych Antonovych as one of the prominent scholars of Ukrainian historiography. The formation and development of his personality and the formation of worldview principles are traced. The specific